Innovative Pedagogical Approaches and Policy Interventions to Enhance Teacher Capacity in Indian Vocational Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This review study takes a look at new ways of teaching and new policies that have been put in place to help vocational schools in India train better teachers. Effective teacher training and capacity building are crucial in connecting conventional education with industrial needs, especially with the growing demand for skill-oriented education. In order to better equip vocational instructors, the research delves into innovative pedagogical practices such blended learning, project-based learning, and experiential education, as well as the use of digital resources. Additionally, it examines the function of policy frameworks, in particular NEP 2020, in fostering professional growth and filling current deficiencies. The article draws on worldwide norms and successful case studies from India to emphasize difficulties like inadequate infrastructure, social and cultural obstacles, and a lack of technological resources. The results highlight the importance of stakeholder engagement, new training approaches, and strong policy execution in improving India's vocational education.